A retrospective analysis of reported errata in five leading medical journals in 2012 - Vijaya R. Bhatt; Madan R. Aryal; Sujana Panta; Kailash Mosalpuria; James O. Armitage (Journal of Community Hospital Internal Medicine Perspectives, 2014)
Background: Although medical publications are frequently used as the source of information, the prevalence of errata remains unclear. The objective of this study was to examine peer-review and publication processes of medical journals as well as to determine the occurrence of reported errata in medical journals and timeliness in identifying and correcting errata. Methods: Five medical journals, New England Journal of Medicine, Annals of Internal Medicine, British Medical Journal, Journal of American Medical Association, and Lancet, were evaluated. The characteristics of these journals were obtained from editors’ survey. All these journals report errata noted in their prior publications. We retrospectively analyzed all errata reported from January 1, 2012, to December 31, 2012. The mean number of reported errata per issue, the most common errata, and the mean time to report errata were calculated. Results: The journals had high impact factors (14–51), received 3,200 to more than 15,000 submissions in 2012, and utilized two or more external reviewers and usually two or more editors for any accepted articles. All the journals edited the accepted articles, including references, figures, and tables for style. A mean of 1.3 articles with ≥1 errata was reported per issue (a total of 306 articles with errata in 226 issues). Errata in author's information, numeric errata, and errata in the figures and tables were the most common errata. The mean time to report the errata was 122 days. Conclusion: The high-impact journals, with extensive pre-publication review, reported relatively few errata per issue. The delay in reporting errata needs further exploration.